2022
DOI: 10.1111/jcal.12759
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mobile technology usage on cognitive, affective, and behavioural learning outcomes in primary and secondary education: A systematic review with meta‐analysis

Abstract: Background The impact of mobile technology usage on student learning in various educational stages has been the subject of ongoing empirical and review research. The most recent meta‐analyses on various types of mobile technology use for potential benefits of learning covered the empirical studies up to about nine years ago. Since then, the use of mobile technology in primary and secondary education has increased tremendously, and numerous empirical studies have been conducted on this topic, but their conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 132 publications
0
3
1
Order By: Relevance
“…We examined if the subject category would moderate the effect of mobile learning on students’ academic achievement. This study found that the subject category had no moderating effect, which is consistent with previous results (Wang et al, 2022) and inconsistent with other findings (Talan, 2020; Zheng et al, 2018). In addition, mobile devices have the best effect on students’ learning in the medical field, the effect is not different in the literature field and the science field, and the effect size is the smallest in combination.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…We examined if the subject category would moderate the effect of mobile learning on students’ academic achievement. This study found that the subject category had no moderating effect, which is consistent with previous results (Wang et al, 2022) and inconsistent with other findings (Talan, 2020; Zheng et al, 2018). In addition, mobile devices have the best effect on students’ learning in the medical field, the effect is not different in the literature field and the science field, and the effect size is the smallest in combination.…”
Section: Discussioncontrasting
confidence: 56%
“…Secondly, many first-order meta-analysis studies have tested the moderating effect of subject category, but the results are inconsistent. For example, Talan (2020) proposed that the application efficacy of mobile learning in science is greater than in mathematics, while others hold the opposite view (Sung et al, 2017; Wang et al, 2023). Moreover, there is some disagreement among researchers about the moderating effect of grade level.…”
Section: Introductionmentioning
confidence: 99%
“…Didactic innovation is important for several reasons: research findings on teaching and learning (e.g., a meta-analysis of research on instruction, learning differentiation, and individualization), changing and diverse student needs, more challenging goals of schooling, and the speed of change and obsolescence of information (Jorgenson, 2006;Valenčič Zuljan & Kalin, 2007). In recent decades, pedagogical innovations have often been associated with the use of ICT (Cetin, 2016;Kukey et al, 2019;Nachmias et al, 2004;Ottestad, 2010;Wang et al, 2023) as student-centered instructional models have been promoted (e.g., active and self-regulated student learning (Bakkenes et al, 2010)). The following is a discussion of one of the didactic innovations, namely the flipped learning and teaching approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These misunderstandings are the causes of the difficulties that e-learning communities experience. Kisanga & Ireson, (2015) assert that teachers' acceptance of e-learning is mostly based on their comprehension, the intrinsic advantages of the e-learning platform, and people's resistance to change, all of which are regarded as individual elements in the adoption of e-learning (Aldowah et al, 2018;Wang, Tigelaar, Zhou & Admiraal, 2022). Aldowah et al, (2019) also emphasized that course, contextual, technological, and individual challenges are pre-existing for the productive use of e-learning by teachers.…”
Section: Introductionmentioning
confidence: 99%